Substantively Constrained Choice and Deference - Holroyd, Jules (Journal of moral philosophy, 2010)
Abstract Substantive accounts of autonomy place value constraints on the objects of autonomous choice. According to such views, not all sober and competent choices can be autonomous: some things simply cannot be autonomously chosen. Such an account is developed and appealed to, by Thomas Hill Jr, in order to explain the intuitively troubling nature of choices for deferential roles. Such choices are not consistent with the value of self-respect, it is claimed. In this paper I argue that Hill's attempt to explain the problem with such a choice, and Marcia Baron's interpretation and defence of his view, fail in this task. The troubling nature of some choices for deference cannot be explained in terms of a substantive self-respect condition for autonomy.